Social and health sector reform towards 2040 in Japan - Tomonori Hasegawa; Kunichika Matsumoto; Ryo Onishi; Koki Hirata (Public Administration and Policy, 2020)
Purpose – The purpose of this paper is to examine the health sector reform toward 2040 of Japan as a super-aged society. Design/methodology/approach – This paper discusses the current healthcare policies adopted in Japan and projects the challenges in future as a super-aged society. Findings – Through Japanese experiences, it is considered that Community-based Integrated Care System is useful, which takes into account the perspective of health care users. Being a super-aged society, it is essential for Japan to have more consensus by further removing obstacles, and paying attention to the change of paradigm and the purpose of care. Originality/value – Based on the case of Japan, this paper serves as a reference for other East Asian countries, which would sooner or later encounter the similar situation of becoming super-aged societies in the 21st century.